2021
DOI: 10.1002/jcla.23922
|View full text |Cite
|
Sign up to set email alerts
|

Immunological characteristics and effect of cyclosporin in patients with immune thrombocytopenia

Abstract: Objective Immune thrombocytopenia (ITP) is well‐known as an antibody‐mediated autoimmune disease, and it is easy to get response but often turns to relapse or refractory. Cyclosporin is a traditional immunosuppressant and had a good effect on ITP patients. In this paper, we retrospectively analyze the immunological characteristics and therapeutic effect of cyclosporin in 220 patients with ITP. Methods All newly diagnosed ITP patients in the Department of Hematology, Tianjin Medical University General Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…A total of 23 reports have been published involving the use of CyA in AIC for a total of 441 patients ( Table 3 ). They were mainly pediatric studies (60%) and included 10 case reports/series, 9 – 18 8 clinical trials, 19 – 26 and 5 retrospective studies 27 31 of CyA used as single agent or in combination.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 reports have been published involving the use of CyA in AIC for a total of 441 patients ( Table 3 ). They were mainly pediatric studies (60%) and included 10 case reports/series, 9 – 18 8 clinical trials, 19 – 26 and 5 retrospective studies 27 31 of CyA used as single agent or in combination.…”
Section: Resultsmentioning
confidence: 99%
“… 29 32 Cyclosporine can regulate abnormal immune cells in patients with ITP, suppress abnormally activated immune responses, and play an important role in the protection of platelets coated with anti-platelet autoantibodies. 12 Related research found that after repeated cyclosporine A administration, two patients with chronic severe refractory ITP experienced long-term complete remission, and their adverse reactions were relatively mild. 33 The results of the present analysis demonstrated that cyclosporine-based combination therapy can effectively improve the condition of patients with a certain degree of safety.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Furthermore, as the main second-line drug for the treatment of ITP, cyclosporine can improve the total effective rate of clinical treatment in patients with ITP and reduce the recurrence rate. 12 , 13 A recent retrospective study found that cyclosporine effectively treated children with refractory ITP and prevented splenectomy. 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complement levels in patients with RA remain controversial, with C3 and C4 levels generally elevated. However, some studies have exhibited that C3 and C4 levels are reduced 4 …”
Section: Classic Ra Indicators Commonly Used In Clinical Diagnosismentioning
confidence: 99%